Effect of propofol-based procedural sedation on risk of adverse events in a French emergency department: a retrospective analysis. (December 2020) - Muller, Barbara; Michalon, Arnaud; Reuillard, Adrien; Holman, Anne Marie; Guihard, Bertrand; Combes, Xavier
Abstract : Objectives: Propofol is widely used today outside the operating room to facilitate painful procedures. The objective of this retrospective study was to evaluate the frequency and type of complications related to a propofol-based procedural sedation protocol used in a French emergency department. Methods: This retrospective study reviewed the records over a 6-year period of all patients—adults and children—who received propofol for procedural sedation according to a pre-established protocol. The frequency and type of adverse events related to this sedation were recorded. Adverse events were classified according to the World Society of Intra-Veinous Anaesthesia International Sedation Task Force as sentinel, moderate, minor, or minimal. Results: During the study period, 602 patients—395 adults (66%) and 207 (34%) children—received propofol. The main indications for procedural sedation were fracture (n = 327) and dislocation (n = 222) reduction, pleural drain placement (n = 34), and abscess incision (n = 12). Among the 602 consecutive cases, we identified 90 adverse events (14.9%; 95% confidence interval: 12–17.7%). These 90 events were classified as 1 sentinel (hypotension episode), 5 moderate (2 airway obstruction and 3 apnea episodes), 83 minor, and 1 minimal risk-averse events. There were no adverse outcomes. Conclusion: Nearly all of the adverse events in our series were minor. In the French medical system, the use of propofol outside the operating room by non-anesthesiologist physicians for procedural sedation appears safe.